THE DISTINCTION BETWEEN REPRESENTATION AND RELATED LEGAL INSTITUTES - Marković, Velisav (Law - Theory and Practice, 2015)
Representation is a way (an option) of taking legal affairs in the name and on behalf of a represented person where all effects of the acts undertaken in the name and for the account of the represented person(s) arise only toward the represented person, if the agent acted within the limits of the powers of representation and informed the third party that the acts were undertaken in the name and on behalf of the represented person. Representation has similarities with the other legal institutes such as a warrant, commission, mediation, the management without a warrant. In this paper, the author analyzes the similarities and differences between representation and aforementioned institutes and clarifies the distinction between them.